2010
DOI: 10.1038/oby.2009.483
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Ecological Momentary Assessment in Pediatric Obesity to Quantify Behavior, Emotion, and Sleep

Abstract: Pediatric obesityRecent estimates show that nearly 32% of children in the United States are overweight, which is dramatically higher than the prevalence reported in the 1980s (ref. 1). Childhood obesity is associated with psychological, neurologic, pulmonary, gastrointestinal, circulatory, and endocrine conditions (2,3). Most pediatric obesity interventions are marked by modest changes in weight or adiposity and substantial relapse (4). More comprehensive assessments documenting specific behavior change are ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 10 publications
(12 reference statements)
3
52
0
Order By: Relevance
“…Adolescents are willing to complete a rigorous protocol to obtain this information. Compliance rates to the physiological monitoring system, accelerometer, and survey questions are similar to those reported in the literature [6] and should be sufficient to recover relationships in the data. In general, the participants were excited about the use of the equipment and reported they would be willing to comply with a similar protocol if requested to do so by their doctor.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…Adolescents are willing to complete a rigorous protocol to obtain this information. Compliance rates to the physiological monitoring system, accelerometer, and survey questions are similar to those reported in the literature [6] and should be sufficient to recover relationships in the data. In general, the participants were excited about the use of the equipment and reported they would be willing to comply with a similar protocol if requested to do so by their doctor.…”
Section: Discussionsupporting
confidence: 57%
“…Ecological momentary assessment in particular has been recommended to increase the efficacy of interventions by clarifying antecedents of physical activity, by improving the accuracy of self-monitoring, and by specifying the temporal relationships of target behaviors [6]. Tools that simultaneously measure interrelated processes can significantly alter clinician's ability to inform treatment and provide feedback on engagement in health behaviors.…”
Section: Original Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…14,15,22 It has not been used to inform behavior and learning in graduate medical education. In our literature review, we found 1 study that used EMA in a family medicine residency program to assess the cognitive impact of electronic knowledge resources.…”
Section: Discussionmentioning
confidence: 99%